2021
DOI: 10.3390/foods10020404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crocus sativus L. Stigmas Microwave Dehydration on Picrocrocin, Safranal and Crocetin Esters

Abstract: The dehydration process is the basis to obtain high quality saffron and to preserve it for a long time. This process modifies saffron’s main metabolites that define its quality, and are responsible for the characteristic color, taste, and aroma of the spice. In this work, the effect of microwave dehydration on saffron main metabolites (picrocrocin, safranal and crocetin esters) from Crocus sativus L. stigmas at three determinate powers and different time lapses was evaluated. The results showed that this dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
(60 reference statements)
1
13
0
Order By: Relevance
“…In all groups, there is a rapid decrease of 7 to 14 days, consistent with that detected by the panelists as shown in Table 2 , and a different increase at each group to 60 days. These findings are consistent with previous findings [ 23 , 85 ] that indicated that safranal concentration is higher in saffron stored longer than a month because of formation of safranal from crocetin esters and picrocrocin during storage [ 28 ]. Previous studies reported that the main compounds of saffron change over time [ 82 , 83 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In all groups, there is a rapid decrease of 7 to 14 days, consistent with that detected by the panelists as shown in Table 2 , and a different increase at each group to 60 days. These findings are consistent with previous findings [ 23 , 85 ] that indicated that safranal concentration is higher in saffron stored longer than a month because of formation of safranal from crocetin esters and picrocrocin during storage [ 28 ]. Previous studies reported that the main compounds of saffron change over time [ 82 , 83 ].…”
Section: Discussionsupporting
confidence: 93%
“…Others [ 49 ] have also reported similar stability in a* and b* in ham slices after 8 weeks of storage in vacuum packaging. The obtained results could be attributed to the presence of crocetin esters, also known as crocins, a group of water-soluble carotenoids responsible for saffron’s color strength [ 23 , 28 , 56 ]. Crocetin is formed from crocins during storage time [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dehydration procedure used affects the main metabolites of saffron that are responsible for these organoleptic characteristics and that define the quality of the product. García-Blázquez et al [ 7 ] studied the effect of microwave dehydration on saffron main metabolites (picrocrocin, safranal and crocetin esters) from Crocus sativus L. stigmas at three determinate powers and different time lapses. A control of saffron dehydrated using the traditional dehydration called “toasting” in which stigmas are put on a sieve with a silk bottom placed over a heating source was obtained and analyzed.…”
mentioning
confidence: 99%
“…Saffron is a highly valued spice that imparts color, flavor, and aroma to food. The compounds responsible for these properties are a group of carotenoids, crocetin sugar Molecules 2021, 26, 2073 2 of 8 esters, picrocrocin, and a wide array of ketones and terpenic aldehydes, with safranal being the most important compound [8]. Picrocrocin is the most important substance responsible for the characteristic bitter taste of saffron [9].…”
Section: Introductionmentioning
confidence: 99%